Post-Conflict Political Dynamics in Aceh and Bangsamoro: Religious Symbols and Patrimonialism in Practice - Syarifah Huswatun Miswar; King Alizon M. Camral (Muslim Politics Review, 2025)
Post-conflict Aceh and Bangsamoro continue to face significant governance challenges marked by ineffective autonomy and the consolidation of religiously-grounded political authority. While special autonomy theoretically provides an inclusive framework for development, in practice, authority remains monopolized by elites who draw legitimacy from Islamic symbols. The rise of figures labeled as ‘abang-abang syar’i’ (male leaders who publicly represent Islam) demonstrates how public displays of piety are often intertwined with patronage, collusion and kinship-based power consolidation. In Aceh, widespread trust in religious scholars conceals an accommodative and hierarchical power structure, while in Bangsamoro, religious rhetoric is strategically deployed to distribute benefits narrowly within elite circles. This study adopts a comparative perspective and a theoretical framework integrating Islamic patrimonialism, moral politics, masculinity, and Islamic neopopulism. The findings suggest that religious symbolism primarily operates as aesthetic legitimation, while entrenched corruption and patronage networks continue to undermine inclusive, accountable, and socially-just governance.